Digital food from paddock to platform - Lewis, Tania (Bloomsbury Academic, 2020)
"Tania Lewis offers the first critical account of the impact of digital information, media, and communication technologies on the topic of food. Lewis critically analyzes how our relationship to food consumption, production, and politics is being re-mediated through digitally connected electronic devices, practices and content. By drawing together the world of food and the digital, the book speaks to a number of pressing contemporary themes including the tensions around digital engagement in increasingly commercialized spaces; the changing nature of politics in a social media context; the growing naturalization of digital devices and related practices of data monitoring; and the role and impact of digitization on social relations. At the forefront of critical new research, and written with a student readership in mind, this text is essential for scholars interested in media studies, cultural studies, food studies, and cultural geography."--
Includes index. - Includes bibliographical references
Ch. 1: Introduction: A Cook's Tour Part 1: Digital Foodscapes Ch. 2: Food Fotos: From Conspicuous Prosumers to Digital Sociality Ch. 3: Ordinary Expertise and Sharing Economies Ch. 4: And On That Farm He Had A...Laptop: Alternative Food Networks and Web 2.0 Part II: Food Politics in a Digital Era Ch. 5: It's Activism, Jim, but not as we know it: From Food Apptivism to Online Protest Ch. 6: FoodInc#: Corporate Food Politics Online Part III: Complicating Connectivity Ch. 7: Cooking in the Cloud Ch. 8: Meal Monitors: From Data to Drones Ch. 9: Conclusion: Governing and Decoding Digital Foodscapes Bibliography -- Index
Keywords: Food & society / bicssc; Food / Social aspects; Digital media / Social aspects; Social media / Social aspects; Food in popular culture; Food / Information services; Kultur; Neue Medien; Lebensmittel; Medientheorie; Electronic books